Deliberate practice, biological maturation, functional performance, and psychosocial characteristics among young basketball players - Lima, Ahlan Benezar (2021)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro de Desportos, Programa de Pós-Graduação em Educação Física, Florianópolis, 2021.